Analyzing the basics and criteria of wife's obedience to husband in employment - Mohammad Hassan Haeri; Seyyed Mahmood Mirnourfakhsh; saeideh masuomi hesary (پژوهش‌های فقهی مسائل مستحدثه)
Analyzing the Rudiments and Criteria for Wife's Obedience to Husband’s Wish in Right to Work in Islamic JurisprudenceMohammad Hassan Haeri *   |   Seyyed Mahmoud Mirnoorbakhsh**   |   Saeideh Masoumi Hessari***Received: 2023 May 28  |   Recieved in revised form: 2023 Jul 2   |   Accepted: 2023 Aug 17   |   Published: 2023 Oct 23AbstractThe issue of a woman's obedience to her husband is rooted in the belief in the man's leadership within the family. This belief is supported by Shariah texts and is commonly accepted by Islamic jurists. Scholars from Islamic schools of thought, including the Jafari sect, have discussed the extent of a woman's obedience to her husband. They consider the preservation of the family's well-being and happiness, as well as the fulfillment of rights, to be the man's primary responsibility as the head (Qawāmiyyah) of the household. However, they also acknowledge that specific requirements, such as the wife's freedom to sexually enjoy herself (Istimtā’) and leave the house, are not universally applicable and should be determined based on individual circumstances. This research, conducted through a descriptive-analytical approach and utilizing library resources, explores the criteria for a wife's obedience to her husband in legal matters, including employment. These criteria are derived from Shariah texts and include factors such as the prohibition of cruelty, greed, and the violation of the wife's rights, as well as the avoidance of harm to her.Haeri, M.H. Mirnoorbakhsh, S.M. & Masoumi Hessari, S. (2023) Analyzing the Rudiments and Criteria for Wife's Obedience to Husband’s Wish in Right to Work in Islamic Jurisprudence. Quarterly of New Perspectives in Islamic Jurisprudence, 1 (1) 236-256. Doi: https://doi.org/.